Enzyme replacement therapy and beyond: in memoriam Roscoe O. Brady, M.D. (1923-2016) - Ries, Markus (Journal of inherited metabolic disease, 2017)
Lysosomal storage disorders are strong candidates for the development of specific innovative therapies. The discovery of enzyme deficiencies is an important milestone in understanding the underlying cause of disease. Being able to replace the first missing enzyme in a lysosomal storage required three decades of dedicated research. Successful drug development for lysosomal storage disorders was fostered by the U.S. Orphan Drug Act. Various optimization strategies have the potential to overcome the current limitations of enzyme replacement therapies. In addition, substrate reduction therapies are an alternative approach to treat lysosomal storage disorders, chemical chaperones enhance residual enzyme activity, and small molecules can facilitate substrate transport through subcellular compartments. Bone-marrow derived multipotent stem cells and gene therapies have received FDA orphan drug designation status. The science of small clinical trials played an essential role: non-neurological endpoints, biomarker, and regulatory alignment are key factors in successful drug development for lysosomal storage disorders. Being able to treat brain disease is the next frontier. This review is dedicated to the memory of Roscoe O. Brady, an early pioneer in the research of lysosomal storage diseases.